PROTECCIÓN DE LAS FAMILIAS MONOPARENTALES Y HOMOPARENTALES: UN RETO PARA EL ESTADO COLOMBIANO FRENTE A LOS DERECHOS DE LA INFANCIA (2020)
The objective of this work was to establish how the Colombian legal system protects the emergence of new family manifestations, different from the traditional or nuclear family, such as, among others, single-parent families and homoparent families, taking into account that these types of families have been spreading for both economic and social reasons. Since this is a theoretical work, an analysis was made of the normative sources relating to the subject, taking as a basis the generalities that give rise to the emergence of these families, reviewing studies and publications on the social conditions of these emerging families, in addition to the regulations issued by the Colombian State which emphasize the protection of the rights of both nuclear and emerging families. In addition, a study was made of the provisions contained in the Constitution concerning the protection of the rights of children as members of the nuclear family, as well as the rulings of the Constitutional Court in its judgements, and it was concluded that this normative development protecting homoparental families, which is based on the right to human dignity, the free development of personality, equality, the right to family and the rights of children, among others, seeks to include minorities, should be highlighted.